The invisible enemy: A systematic review and meta-analysis of maternal smokeless tobacco use as a risk factor for low birth weight. - Akanksha Mahajan; Bhawna Gupta; Michael Tong (PLoS ONE)
Introduction Smokeless tobacco use is a growing public health concern, with potential adverse implications for foetal outcomes if consumed during pregnancy. Birth weight is an important predictive measure for health outcomes of a child throughout their lifespan. Despite extensive literature, it is unclear whether smokeless tobacco consumption during pregnancy has an adverse effect on birth weight. Hence, this review was conducted to determine whether an association exists between maternal smokeless tobacco consumption during pregnancy and birth weight of infants. Methods Systematic literature search was performed in Medline (via PubMed), Embase, Scopus, and CINAHL with no restrictions on language or time until May 2024. All observational studies that examined the relationship between maternal smokeless tobacco use and low birth weight of infants were eligible for inclusion. Methodological quality of included studies was assessed using the Newcastle Ottawa Scale. Results Thirty-three studies were eligible for the review, including twenty-eight cohort, three case-control and two cross-sectional studies. A statistically significant association between use of smokeless tobacco and low birth weight was reported in thirteen studies. Eleven studies reported a statistically significant reduction in mean birth weight in maternal smokeless tobacco users. Pooled estimates of eighteen studies with 733,061 participants showed that there was a statistically significant association (OR = 2.25 [1.63, 3.11] P<0.001); between maternal smokeless tobacco use during pregnancy and low birth weight. Subgroup analysis found a significant association between mishri consumption during pregnancy and low birth weight (n = 646 participants, OR = 10.98 [2.03, 59.34], P = 0.005), but not betel nut (n = 8007 participants, OR = 1.02 [0.84, 1.25]), betel quid (n = 483 participants, OR = 1.51 [0.47, 4.89]) or khat (n = 475 participants, OR = 1.41 [0.64-3.09]). Conclusions This review presents an association between maternal smokeless tobacco use and low birth weight, and reduction in mean birth weight. It is suggested that cessation and reduction of maternal smokeless tobacco use should receive specific attention within routine prenatal care. Implications The results of this study highlight the need for further preventive public health campaigns to create awareness about detrimental effects of smokeless tobacco on foetal outcomes. Patient education in the primary care setting will aid in promoting smokeless tobacco cessation prior to pregnancy.